Appreciative learning approach: a new pedagogical option - Eow, Yee Leng; Wan Ali, Wan Zah; Mahmud, Rosnaini; Baki, Roselan (Faculty of Educational Studies, Universiti Putra Malaysia, 2010)
This is a theoretical paper in which authors attempt to present appreciative learning approach as a new pedagogical option for educational setting. The paper starts with the description of Appreciative Inquiry (AI) as both theory and practice. Next, it discusses the eight principles of AI in relations to the current trend of learning. Then, the 4Ds (Discovery, Dream, Design, Destiny) model of AI that facilitates the practice of appreciative learning approach is illustrated. Authors propose some amendments to the initial model in order to promote more flexibility adapting to the aggressive technology progression. Subsequently, some thought provoking questions and recommendations for future researches are formulated at the end of the paper.